Preparation of Iron-Doped SiO2/TiO2 Using Silica from Sugarcane Bagasse Ash for Visible Light Degradation of Congo Red - Nawwal Hikmah; Dewi Agustiningsih; Nuryono Nuryono; Eko Sri Kunarti (Universitas Gadjah Mada, 2021)
Iron(III)-doped SiO2/TiO2 composite (SiO2/TiO2-Fe) has been prepared from sugarcane bagasse ash for photocatalytic degradation of Congo Red. This research was initiated by preparing SiO2 from sugarcane bagasse ash through a sol-gel method. The SiO2/TiO2-Fe was obtained by mixing SiO2 gel with TiO2-Fe sol which was produced with titanium tetraisopropoxide (TTIP) as precursor and FeCl3·H2O as the dopant source. Dopant concentration was varied by 0, 1, 3, 5, 7% (w/w). The prepared materials were characterized by FT-IR, XRD, SR-UV, XRF, SAA, and SEM-EDX. The photocatalytic activity was evaluated for Congo Red degradation in a closed reactor under visible light illumination. The degradation yield was determined by the UV-Visible spectrophotometry method. Results showed that SiO2 was successfully extracted from bagasse ash with a silica content of 90.87%. The SiO2/TiO2-Fe composite was successfully prepared with the bandgap energy value (Eg) decreasing as the dopant concentration increased. The optimum Eg of 2.63 eV was obtained at the concentration of Fe was 5%. Under that condition, the SiO2/TiO2-Fe photocatalyst degraded Congo Red solution by 98.18 % under visible light at pH 3 with a mass of 30 mg for 90 min. The SiO2/TiO2-Fe composite is expected to be a photocatalyst material candidate for dye wastewater treatment.